PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP EFEKTIVITAS PEMIMPIN DI SAMABE BALI SUITE AND VILLAS - Surya Purnama, Ni Wayan; Surya Putra, Made (E-Jurnal Manajemen, 2016)
The aim of this research is to know the influence of transformational leadership on leaders effectiveness in Samabe Bali Suite and Villas. The number of samples taken as much as 108 employee, by the proportional random sampling method. Data collection through interview and survey using questionnaire as the appliance. Data analysis technique that is used is simple linear regression. Based on the results of the analysis found that transformational leadership have positive impact on the leader effectiveness.
Keywords: Leader Effectiveness, Transformational Leadership